Shaping Africa's Higher Education: Future Directions for Research - Tamrat, Wondwosen (International Higher Education, 2025)
<h3 id="continental-aspirations-for-african-higher-education-emphasize-the-need-for-comprehensive-reforms-in-access-equity-quality-financing-governance-international-partnership-research-and-innovation-and-community-engagement-changes-and-future-research-in-these-critical-areas-will-enable-african-higher-education-institutions-to-contribute-their-share-to-the-continents-transformation-on-par-with-the-rest-of-the-world" data-pm-slice="1 1 []">Continental aspirations for African higher education emphasize the need for comprehensive reforms in access, equity, quality, financing, governance, international partnership, research and innovation, and community engagement. Changes and future research in these critical areas will enable African higher education institutions to contribute their share to the continent’s transformation on par with the rest of the world.